Research of prevalence of polymorphism of the TLR 9 type gene in patients with infectious mononucleosis, caused by Epstein-Barr virus - Liadova, Tatiana (ScienceRise: Medical Science, 2017)
There was studied the prevalence of -1486 T/C polymorphism of TLR-9 gene in 52 patients with infectious mononucleosis (IM), caused by Epstein-Barr virus. Three main genotypes of - 1486 T/C of TLR-9 gene: TT, TC, CC were identified based on obtained results. The study of the frequency of appearance of separate genotypes in patients with IM revealed the dominance of CC and TT genotypes compared with the control group. The study of the distribution frequency of -1486 T/C-polymorphism of TLR-9 gene for different genotypes demonstrated the specificity of CC genotype changes in patients with IM and the absence of such changes for TT and TC genotypes. Aim of research. The study of the frequency of - 1486 T/C polymorphism of TLR-9 gene in patients with IM, caused by Epstein-Barr virus. Materials and methods. The study for determining -1486 T / C polymorphism of TLR-9 gene was realized in 52 patients with IM. Among them women - 31 (59,6 %), men - 21 (40,4 %) in the age diapason from 18 to 34 years. The control group for studying the prevalence of - 1486 T/Cpolymorphism of TLR-9 gene consisted of 40 healthy donors. The mean age 24,2 ± 2,4 years, from 18 to 44 years. For revealing DNA of EBV by the method of the reverse transcription of PCR with hybridization-fluorescent detection of amplification products, sets of reagents Amplisens (Russia) were used. The polymorphic zone - 1486 T / C, rs187084 of TLR9 gene was used by PCR amplification in real time by determining the length of restrictive fragments of PCR using Ncol restrictive fragment and oligonucleotide primers. Results. The analysis of results of - 1486 T/C polymorphism of TLR-9 gene allowed to identify three main genotypes - TT, TC, CC. The study of the frequency of separate genotypes detection allowed to establish the prevalence of CC and TT genotypes compared with the heterozygotic TC genotype. The study of the distribution frequency of -1486 T/C-polymorphism of TLR-9 gene for different genotypes demonstrated the specificity of CC genotype changes in patients with IM and the absence of such changes for TT and TC genotypes. Our research established the correlation between - 1486 TLR-9 C/Cpolymorphism with IM that proves the important role of mediated TLR signalization in the pathogenesis of EBV infection. The study of genes polymorphism among receptors that take part in recognizing a virus is necessary for determining the genetic background, connected with the infection risk, disease course and possible IM results. It allows to reveal risk groups among patients and to carry out the timely therapy. Conclusions: 1. It was proved, that - 1486 T/C polymorphism of TLR-9 gene is detected reliably more often in patients with IM than in the control group. 2. The distribution of -1486 Т / С polymorphism of TLR-9 allowed to reveal the association of CC genotype with manifest forms of IM